Penerapan Metode Case-Based Reasoning (CBR) untuk Anamnesa Gejala Kelainan Kelamin pada Bayi Laki-Laki - Gifari I. S. Awam; Mahardika I. Takaendengan; Chriestie E.J.C. Montolalu (Sam Ratulangi University, 2022)
Parents certainly want their children to be born perfectly without any abnormalities, including the male genitalia. Some of the disorders that are often found in the male genitalia include phimosis, hypospadias, epispadias and cryptorchidism. This study aims to design a system that performs anamnesis by applying the Case Based Reasoning (CBR) method to the symptoms of genital abnormalities in male infants. The stages of the CBR method are 1) retrieve which refers to similar cases, 2) reuse namely reusing information from the case, 3) revise which is correcting the solution if needed, and 4) retain which is storing the revised results. The results showed that the application of the CBR method to anamnesis for symptoms of genital abnormalities in male infants was successfully carried out, where the anamnesis system used the CBR method in accordance with manual calculations with similarity tests and direct testing by experts. In the case example, the results of the system history and manual CBR calculations have the same probability or possibility of experiencing phimosis disorders by 100% and hypospadias disorders by 37.5%.